Study on Production and Quality Evaluation of Biscuits Made From the Blend of Cow Peas and Wheat Flour: Exploring the potential of cowpea-wheat flour blends in biscuit production (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Cowpea is a sub-Saharan African indigenous legume and is primarily grown as an intercrop with millets, sorghum, groundnut and maize in the dry savanna regions. In certain parts of the tropics, protein-rich cowpea grains are eaten in various ways. In West Africa, the average cowpea grain yield is approximately 492 kgha, which is much lower than its potential yield. Wheat is the most significant food grain in the world, on the other hand. It provides the citizens of the world with around 20 percent of the total calories and proteins of food. In 43 countries, it is the main staple for at least 35 percent of the world's population. In Europe, over 30 percent of food calories are derived from wheat, while in some South-East Asian countries, where rice is the staple, less than 10 percent of calories are derived from wheat. Reliance on wheat varies widely with the geographical region. The effect on the rheological, baking and sensory characteristics of biscuits of blending 50 to 250 g kg-1 cowpea flour into wheat flour will be studied. The prevalence of protein energy malnutrition in developing economies is growing, especially in Kenya, owing to poverty and the dependence of consumers on plant sources to meet their energy needs. Food diversification is one method to eradicate the malnutrition of protein energy, and pulses have the ability to be used in cereal products to improve protein quality. For this purpose, different varieties of wheat will be used for the preparation of flour blends which, in this case, will be further assessed for their quality and potential application in baked goods, such as biscuits. Five blending ratios, including B1 (9010), B2 (4060), B3 (6535), B4 (7822), and B5 (5347), respectively, will be prepared for the wheat and cowpea flour blends. For flour blend formulation, the D-optimal programmer for mixture design will be used. Biscuit and extruded cowpea and wheat blend products will be examined. Physical, functional, proximate, mineral and microbial consistency are the criteria of the quality characteristics to be used in value-added items. In addition, it will also investigate bioactive components and sensory consistency assessment. The biscuit samples will be prepared for a 10-minute holding time at a baking temperature of 205 °C. Extruded samples are also provided at feed moisture (18 and 21), barrel temperature (100, 110 and 120 °C) and screw velocity (175 and 220 rpm).